Perspectiva histórica das políticas hidráulicas no Brasil e na Espanha - Briz, Esther María Sánchez (2018)
The purpose of this paper is to understand the situation, context, management, paradigm shifts and the formulation of public policies related to in Brazil and in Spain, with a historical journey to the current situation. During this analysis it is aimed at identifying possible similarities and differences. For the elaboration of the dissertation an extensive revision of texts was carried out, including articles scientific, books, laws, internet sites and academic work. The reason for analyzing two countries distinctive features arise when identifying a common origin due to the geographical proximity of the Portugal and Spain as member countries of the Iberian peninsula, followed by independence of Portugal in 1139 and discovery of Brazil in the year 1500. Subsequently, Brazil and Spain they navigate different paths and develop their own resource management policies water resources. In the last decades, from new perspectives of global scope in the sector of the Governments of both countries are promoting new objectives, approaches, methods and institutional changes in search of the sustainable and integrated use of water resources that guarantee supply for present and future generations. With the idea of ​​facilitating the understanding of the text was divided into several sections. The first three are intended to provide an overview of the geography, water reality, historical approximation and resource skills water resources. The following sections analyze relevant aspects that characterize the management of waters: ownership, uses, political-institutional system, economic value and hydraulic works. Finally, a list of current legislation is included. The scope of study of the work adjusted to surface fresh waters; marine waters, groundwater and climatic periods extremes such as droughts in northeastern Brazil are not included in the main objective of the study, but in several sections they deal with a better understanding of the situation. In essence, the study detects periods in which the practices and paradigms present similarities in the two countries. Although the two countries have climatic, hydrological and cultural different, it was possible to verify that both started to adopt the same paradigms of the management of waters, a fact that reflects the international acceptance of the paradigm of sustainable development.